Introduction: 50 years after the General Education Act of 1970 - Fernández Soria, Juan Manuel; Sevilla Merino, Diego (Historia y Memoria de la Educación, 2021)
The commemorative opportunity is only a circumstance that prompts to investigate the General Education Act (LGE) of 1970 fifty years after its approval. Another more essential reason invites its study: to investigate with new analyzes and new perspectives on what the LGE meant for the modernization of the country and for the transition between Franco’s education and constitutional education. This requires examining the precedents of the 1970 Law and paying attention to the place that the LGE has occupied in educational historiography, in which an evolution towards current historiographic trends is visible. In these highlights the study of international influences in the process of educational modernization, the different iconographic discourses with which the LGE is represented, the protagonism of some of its traditional actors, the rereading of timeless themes present in the Law, and the debates that this generates in the collective memory. These questions are addressed here from the historian’s workshop, which are enriched on this occasion with testimonies of individual memories, protagonists in the gestation, development and application of the 1970 Law.